Special binder for granulated fertilizer and preparation method thereof
By constructing an organic-inorganic hybrid structure of starch-grafted polymer and chitosan-modified zeolite, the problems of easy pulverization and instability of binders in high-nitrogen compound fertilizers were solved, and the particle strength and slow-release performance were improved, making it suitable for the stability and environmental friendliness of high-nitrogen compound fertilizers.
Patent Information
- Application Number
- CN202511866664.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-11
- Publication Date
- 2026-01-23
AI Technical Summary
Existing binders are prone to pulverization, nutrient dilution, and instability in high-nitrogen compound fertilizers. Traditional clay binders have poor dispersibility, and glutaraldehyde crosslinking agents are prone to failure in high-nitrogen environments, affecting fertilizer strength and storage stability.
An organic-inorganic hybrid structure was constructed by using starch-grafted polymers and chitosan-modified zeolite. Through multiple intermolecular forces, a stable three-dimensional network was formed, which enhanced the particle strength and sustained-release performance.
It improves the strength, anti-pulverization and slow-release properties of fertilizer granules, making it suitable for high-nitrogen compound fertilizers. It has the advantages of good stability and environmental friendliness, and solves the problem of binder failure in high-nitrogen environments.
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of fertilizer additives, and particularly relates to a special binder for granular fertilizer and a preparation method thereof. BACKGROUND
[0002] As a high-efficiency fertilizer form widely used in modern agriculture, granular fertilizer realizes precise proportioning and slow-release supply of basic nutrients such as nitrogen, phosphorus and potassium by mixing and granulating the powdery filler with the basic nutrients, and plays an important role in improving crop yield and fertilizer utilization rate. However, the powdery material itself has poor adhesion, and has inherent defects such as difficulty in granulation, low granule strength, easy powdering and caking in storage and transportation, which seriously affect its application effect.
[0003] In order to overcome the above molding problems, a special binder needs to be added in the granulation process to give the powdery material good molding property through physical adhesion or chemical bonding. Although the clay mineral binder widely used in production has the advantage of low cost, its adhesion ability is limited, and a high addition proportion is often needed to realize basic granulation, which not only significantly dilutes the effective nutrient content in the fertilizer and increases the transportation cost of unit nutrient, but also causes the inhomogeneous nutrient content among the fertilizer granules due to the poor dispersion uniformity of clay in the material. In the drying process, the clay material is easy to powder and fall off on the surface of the granules to produce dust, affecting the production environment and product qualification rate. More seriously, long-term application of the fertilizer containing a large amount of clay may cause the accumulation of ineffective components in the soil, which may lead to soil compaction and adversely affect the sustainable development of agriculture.
[0004] The Chinese patent with the publication number CN103011959B discloses a binder for granular fertilizer and a preparation method thereof. By using the "starch-aldehyde" crosslinking technology, the adhesion property of the binder is improved to a certain extent. The technology uses aldehyde crosslinking agent to react with the hydroxyl groups in the starch molecules to form a crosslinking network, thereby enhancing the film-forming property and water resistance of the binder, and better solving the problems of poor dispersion and high addition amount of clay binder.
[0005] However, the aldehyde crosslinking agent such as glutaraldehyde used in the patent scheme has obvious defects in the high-nitrogen fertilizer environment. In the rolling drying and subsequent storage process of fertilizer granulation, the nitrogen-containing fertilizers such as urea and ammonium nitrate will absorb moisture and decompose to release ammonia, forming a local alkaline environment. Under this condition, the active aldehyde group of glutaraldehyde is easy to have a Schiff base side reaction with ammonia, not only consuming effective crosslinking agent and destroying the preset "starch-aldehyde-starch" crosslinking network, but also having a catalytic hydrolysis effect on the glycosidic bond of the starch molecule, leading to the degradation of the molecular chain. The synergistic effect of the two mechanisms causes the adhesion property to rapidly decline during storage, and finally leads to the decrease of the strength of the fertilizer granules and the powdering and caking, which is difficult to meet the stringent requirements of high-nitrogen compound fertilizer on the ammonia resistance and hydrolysis resistance of the binder. SUMMARY
[0006] The present application aims to provide a special binder for granular fertilizer and a preparation method thereof, which constructs an organic-inorganic hybrid structure by the flexible network of starch grafting polymer and the rigid framework of chitosan modified zeolite, forms a stable three-dimensional network by using multiple intermolecular forces, and can simultaneously improve the strength, anti-pulverization and slow-release performance of fertilizer particles, is suitable for high-nitrogen compound fertilizer granulation, can effectively solve the problem of adhesion failure caused by ammonia release, and has the advantages of good stability, environmental friendliness and simple process.
[0007] The purpose of the present application can be achieved by the following technical solutions:
[0008] A preparation method of a special binder for granular fertilizer, comprising the following steps:
[0009] Step one: corn starch and acetic anhydride are used as raw materials to perform esterification reaction under the action of an alkaline catalyst, and acetic ester starch is obtained.
[0010] Step two: through free radical grafting copolymerization reaction, acrylic acid and acrylamide are used as comonomers to introduce acrylic acid-acrylamide copolymer side chains on the molecular chain of acetic ester starch, and a starch grafting polymer solution is obtained.
[0011] Step three: using the principle of electrostatic self-assembly, chitosan is coated on the surface and pores of acid-activated zeolite, and chitosan modified zeolite is obtained.
[0012] Step four: through a composite blending method, the inorganic phase suspension mixed with chitosan modified zeolite and water is compounded with the starch grafting polymer solution, and then is aged, dried and crushed to obtain a special binder for granular fertilizer.
[0013] Further, the specific preparation steps of the special binder for granular fertilizer are as follows:
[0014] The starch grafting polymer solution and the inorganic phase suspension are added into a reaction kettle, and continuous stirring is performed at 50-60 DEG C and 400-600 r / min for 4-6 h, the obtained composite slurry is aged at room temperature for 2-4 h, the aged slurry is suction filtered, the filter cake is washed, dried, ground and refined, and then is passed through a 100 mesh sieve to obtain the special binder for granular fertilizer.
[0015] Further, the mass ratio of the starch grafting polymer solution and the inorganic phase suspension is 80-100:9-11.
[0016] Further, the inorganic phase suspension is mixed by chitosan modified zeolite powder and deionized water in a use amount ratio of 45-55 g:500-800 mL.
[0017] Further, the specific preparation steps of the starch grafting polymer solution are as follows:
[0018] The acetic acid esterified starch and distilled water are added into a reaction kettle, and pasting reaction is carried out at 78-82℃ and 200-300r / min for 1h, then the system is cooled to 60-65℃, ammonium persulfate is added, and stirring reaction is carried out for 15min, then acrylic acid and acrylamide are mixed and added dropwise into the reaction kettle within 1-2h, after the dropwise addition is completed, the reaction is continued for 2-3h, after the reaction is completed, the system is cooled to room temperature, and the product is discharged, to obtain a starch graft polymer solution.
[0019] Further, the amount ratio of acetic acid esterified starch, distilled water, ammonium persulfate, acrylic acid and acrylamide is 400-500g:3.6-4.5L:8-15g:50-100g:33-66g.
[0020] Further, the specific preparation steps of the acetic acid esterified starch are as follows:
[0021] The natural starch and deionized water are added into a reaction kettle, and stirring is carried out at 200-300r / min, a 5% sodium carbonate solution is added to adjust the pH value of the system to 8-8.5, and acetic anhydride is slowly added into the kettle within 20-30min under stirring at 28-32℃ and 150-250r / min, during which the sodium carbonate solution is continuously added dropwise to maintain the pH value of the system at 8-8.5, after the dropwise addition is completed, the stirring reaction is continued for 1h, 0.5mol / L dilute hydrochloric acid is added into the reaction kettle to adjust the pH value to 6.5-7 to terminate the reaction, the product is suction filtered, the filter cake is washed with deionized water until the last washing liquid is neutral, dried, crushed, and passed through a 100 mesh sieve, to obtain the acetic acid esterified starch.
[0022] Further, the amount ratio of corn starch, deionized water and acetic anhydride is 500-700g:900-1300mL:23-32mL.
[0023] Further, the natural starch is any one of corn starch and cassava starch.
[0024] Further, the specific preparation steps of the chitosan modified zeolite are as follows:
[0025] The acid-treated zeolite powder, chitosan and a 1% hydrochloric acid solution are added into a reaction kettle, and continuous reaction is carried out at 60℃ and 100-200r / min for 24h, the pH value of the system is adjusted to neutral with 1.25mol / L sodium hydroxide solution to terminate the reaction, the obtained slurry is subjected to solid-liquid separation, the solid is vacuum dried, ground and passed through a 200 mesh sieve, to obtain a chitosan modified zeolite powder.
[0026] Further, the amount ratio of the acid-treated zeolite powder, chitosan and the hydrochloric acid solution is 50-60g:5-6g:7.5-9L.
[0027] Further, the acid-treated zeolite powder is prepared by using 50-80g of zeolite powder and 500-800mL of 10% hydrochloric acid solution.
[0028] Advantages of the present application:
[0029] 1. The present application constructs an organic-inorganic hybrid structure of "acetate starch graft copolymer" flexible bonding network and "chitosan modified zeolite" rigid porous framework, forms a stable three-dimensional composite system by the synergy of multiple hydrogen bonds, electrostatic adsorption and hydrophobic interaction; fundamentally solves the problems of high addition amount of traditional binders, easy pulverization, dilution of nutrients and easy failure of chemical crosslinking agents in high nitrogen environment due to the action of ammonia, improves the strength, anti-pulverization and slow-release performance of the fertilizer particles, and has the advantages of simple process and environmental friendliness, which is suitable for the prilling of high-performance compound fertilizer such as high-nitrogen compound fertilizer, and realizes the unity of high strength, long-acting slow release and storage stability.
[0030] 2. The present application modifies starch by acetylation, introduces acetyl groups which effectively destroy the crystal structure of starch molecules, reduce the gelatinization temperature, and improve the cold water solubility and reactivity, creating favorable conditions for subsequent efficient graft copolymerization. More importantly, the hydrophobic ester groups of acetate starch produce hydrophobic interaction with the graft polymer chains and chitosan molecules on the surface of zeolite, enhancing the interfacial compatibility between organic and inorganic phases, and providing key synergistic effect for constructing a dense and stable hybrid structure.
[0031] 3. The present application introduces acrylic acid-acrylamide copolymer branches on the acetate starch skeleton, and constructs a polymer network rich in active functional groups such as carboxyl and amide groups. This network not only provides excellent bonding performance through strong hydrogen bonding, but also forms dynamic ion crosslinking points by chelating with calcium, magnesium and other metal ions in the soil through its carboxyl groups, thereby further enhancing the stability of the particle structure and precisely controlling the release of nutrients. In addition, these polar groups produce strong intermolecular interaction with the active groups on the surface of chitosan modified zeolite, realizing the firm combination of flexible polymer network and rigid inorganic framework, and synergistically improving the overall mechanical properties and slow-release function.
[0032] 4. The present application transforms zeolite from an inert filler to a functional reinforcing body by acid activation and chitosan electrostatic self-assembly coating. Acid activation significantly improves the specific surface area and adsorption capacity of zeolite, and chitosan coating introduces abundant amino and hydroxyl groups. The chitosan modified zeolite thus prepared serves as an efficient rigid support point to disperse stress and improve mechanical strength on one hand, and its porous structure and surface functional groups can be tightly interwoven with the starch graft polymer network to jointly construct a "double barrier" to control nutrient diffusion, thereby significantly enhancing the slow-release performance of the fertilizer. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the present application.
[0034] Embodiment 1: A preparation method of a special binder for granular fertilizer, comprising the following steps:
[0035] S1: 600 g of corn starch and 1100 mL of deionized water are added to a reaction kettle, stirred at a rotation speed of 250 r / min, and a sodium carbonate solution with a mass fraction of 5% is added to adjust the pH value of the system to 8; 28 mL of acetic anhydride is slowly added to the kettle under the conditions of a temperature of 30 ℃ and a rotation speed of 200 r / min within 25 min, and a sodium carbonate solution is continuously added dropwise to maintain the pH value of the system at 8 during the process; after the dropwise addition is completed, the stirring reaction is continued for 1 h; 0.5 mol / L of dilute hydrochloric acid is added to the reaction kettle to adjust the pH value to 6.8 to terminate the reaction; the post-reaction product is subjected to suction filtration; the filter cake is washed with deionized water until the last washing liquid is neutral; after drying, crushing and passing through a 100-mesh sieve, acetic ester starch is obtained.
[0036] An alkali-catalyzed esterification method is adopted, corn starch is used as a raw material, the hydroxyl groups on the molecular chain are activated under alkaline conditions, and a nucleophilic substitution reaction occurs between the activated hydroxyl groups and slowly added acetic anhydride, so that the hydrogen on the hydroxyl group is replaced by an acetyl group, an acetic ester starch with a low degree of substitution is generated, the crystalline structure of the starch is destroyed, and a hydrophobic group is introduced; after acid neutralization termination, filtration, washing and drying, the acetic ester starch which is easily soluble in cold water and has significantly improved binding performance is obtained.
[0037] S2: 450 g of acetic ester starch and 4.05 L of distilled water are added to a reaction kettle, and gelatinization reaction is carried out at a temperature of 80 ℃ and a rotation speed of 250 r / min for 1 h; then the system is cooled to 62 ℃, 11.5 g of ammonium persulfate is added, and the system is initiated at the temperature and rotation speed for 15 min; then a mixed monomer composed of 75 g of acrylic acid (AA) and 50 g of acrylamide (AM) is slowly added dropwise through a constant-pressure dropping funnel within 1.5 h; after the dropwise addition is completed, the system is continuously reacted at a constant temperature of 62 ℃ for 2.5 h; after the reaction is completed, the system is cooled to room temperature and discharged, and a starch grafted polymer solution is obtained.
[0038] Based on the principle of water phase free radical graft copolymerization, the crystalline region of starch granules is first destroyed by heating gelatinization to expose active sites, and then free radicals are generated by thermal decomposition of ammonium persulfate to form active centers on the starch skeleton, thereby initiating copolymerization of acrylic acid and acrylamide mixed monomers to "graft" synthetic polymer branches with hydrophilicity, strong hydrogen bonding and metal ion chelating function on the starch molecules. By controlling the monomer drop rate and reaction temperature, the controlled growth of polymer chains is ensured, and finally a starch graft copolymer solution integrating biodegradability and high performance is obtained.
[0039] S3: 65 g of zeolite powder was added to 650 mL of 10% mass fraction hydrochloric acid solution, and was stirred in a constant temperature water bath at 70°C for 2 h. The product was centrifuged, washed with deionized water until the supernatant was neutral, and the washed product was dried at 105°C for 12 h, ground to 200 mesh, and obtained as acid-treated zeolite powder;
[0040] 55 g of acid-treated zeolite powder, 5.5 g of chitosan, and 8.25 L of 1% mass fraction hydrochloric acid solution were added to a reaction kettle, and reacted at a temperature of 60°C and a rotation speed of 150 r / min for 24 h. The pH value of the system was adjusted to neutral with 1.25 mol / L sodium hydroxide solution to terminate the reaction. The obtained slurry was subjected to solid-liquid separation, and the solid was vacuum dried, ground and sieved to 200 mesh to obtain chitosan-modified zeolite powder.
[0041] Based on the principle of acid activation and electrostatic self-assembly, the amino groups on the chitosan molecular chain were protonated and fully dissolved in dilute hydrochloric acid, and the strong electrostatic interaction between the positive charge of the protonated amino groups and the negative potential of the acid-treated zeolite surface caused the chitosan molecules to be tightly coated on the surface and pores of the zeolite particles through interfacial electrostatic self-assembly. Then, the chitosan was deprotonated and deposited by neutralization with alkali, and finally a core-shell structure composite powder was formed with zeolite as the rigid skeleton and chitosan as the organic functional layer.
[0042] S4: 50 g of chitosan-modified zeolite powder and 650 mL of deionized water were added to a stirred tank and dispersed at a temperature of 45°C and a rotation speed of 700 r / min for 1.5 h to obtain an inorganic phase suspension. Then, 450 g of starch graft polymer solution and 50 g of inorganic phase suspension were added to a reaction kettle and stirred at a temperature of 55°C and a rotation speed of 500 r / min for 5 h to allow the polymer chains to be fully adsorbed and coated on the surface of the zeolite particles. The above composite slurry was allowed to stand at room temperature for 3 h, and the aged slurry was filtered. The filter cake was washed with deionized water for 3 times, and the washed wet filter cake was dried at a temperature of 55°C. The dried filter cake was ground and sieved to 100 mesh to obtain a granular fertilizer special binder.
[0043] The organic-inorganic composite binder is prepared by solution compounding-adsorption crosslinking method, chitosan modified zeolite is used as rigid and porous functional unit, and its huge specific surface and surface activity are used as anchoring points; starch grafting polymer is used as flexible and functional group rich binding network precursor; under suitable temperature and shear field, the long chain of polymer is adsorbed, inserted and coated on the surface and pores of zeolite particles through various intermolecular forces such as hydrogen bond, electrostatic adsorption and van der waals force, and a three-dimensional interpenetrating hybrid structure with zeolite as rigid skeleton and polymer as flexible binding network is formed after standing and curing.
[0044] Example 2: A preparation method of a special binder for granular fertilizer, comprising the following steps:
[0045] S1: 500g of corn starch and 900mL of deionized water are added to a reaction kettle, stirred at a speed of 200r / min, and a 5% sodium carbonate solution is added to adjust the pH value of the system to 8; 23mL of acetic anhydride is slowly added to the kettle under the conditions of a temperature of 28℃ and a stirring speed of 150r / min within 20min, and sodium carbonate solution is continuously added to maintain the pH value of the system at 8 during the process; after the addition is completed, the reaction is continued for 1h; 0.5mol / L of dilute hydrochloric acid is added to the reaction kettle to adjust the pH value to 6.5 to terminate the reaction; the post-reaction product is filtered, the filter cake is washed with deionized water until the last washing liquid is neutral, dried, crushed to pass through a 100 mesh sieve, and acetylated starch is obtained.
[0046] S2: 400g of acetylated starch and 3.6L of distilled water are added to a reaction kettle, and gelatinization reaction is carried out at a temperature of 78℃ and a stirring speed of 200r / min for 1h; then the system is cooled to 60℃, 8g of ammonium persulfate is added, and the system is initiated at this temperature and speed for 15min; then a mixed monomer composed of 50g of acrylic acid (AA) and 33g of acrylamide (AM) is slowly added through a constant pressure dropping funnel within 1h; after the addition is completed, the reaction is continued at 60℃ for 2h; after the reaction is completed, the temperature is lowered to room temperature, and a starch grafting polymer solution is obtained.
[0047] S3: 50g of zeolite powder is added to 500mL of 10% hydrochloric acid solution, magnetically stirred in a 70℃ constant temperature water bath for 2h, centrifuged, washed with deionized water until the supernatant is neutral, dried at 105℃ for 12h, ground to pass through a 200 mesh sieve, and an acid treated zeolite powder is obtained.
[0048] The 50 g acid-treated zeolite powder, 5 g chitosan and 7.5 L of 1% by mass hydrochloric acid solution were added into a reaction kettle, and the reaction was continuously carried out at a temperature of 60°C and a rotation speed of 100 r / min for 24 h. The pH value of the system was adjusted to neutral by using a 1.25 mol / L sodium hydroxide solution to terminate the reaction. The obtained slurry was subjected to solid-liquid separation, and the solid was vacuum dried, ground and sieved through a 200 mesh screen to obtain the chitosan-modified zeolite powder.
[0049] S4: 45 g of the chitosan-modified zeolite powder and 500 mL of deionized water were added into a stirred kettle, and high-speed shearing dispersion was carried out at a temperature of 45°C and a rotation speed of 600 r / min for 1 h to obtain an inorganic phase suspension; then, 400 g of the starch graft polymer solution and 45 g of the inorganic phase suspension were added into a reaction kettle, and composite stirring was continuously carried out at a temperature of 50°C and a rotation speed of 400 r / min for 4 h to allow the polymer chains to be fully adsorbed and coated on the surface of the zeolite particles. The above composite slurry was allowed to stand and mature at room temperature for 2 h. The matured slurry was subjected to suction filtration, and the obtained filter cake was washed with deionized water for 2 times. The washed wet filter cake was dried at a temperature of 45°C, and then ground by a flour mill and sieved through a 100 mesh screen to obtain the granular fertilizer special binder.
[0050] Example 3: A preparation method of a granular fertilizer special binder, comprising the following steps:
[0051] S1: 700 g of corn starch and 1300 mL of deionized water were added into a reaction kettle, and stirring was carried out at a rotation speed of 300 r / min. A 5% by mass sodium carbonate solution was added to adjust the pH value of the system to 8.5. 32 mL of acetic anhydride was slowly added into the kettle within 30 min at a temperature of 32°C and a rotation speed of 250 r / min. A sodium carbonate solution was continuously added dropwise to maintain the pH value of the system at 8. After the dropwise addition was completed, the reaction was continuously stirred for 1 h. A 0.5 mol / L dilute hydrochloric acid solution was added into the reaction kettle to adjust the pH value to 7 to terminate the reaction. The post-reaction product was subjected to suction filtration. The filter cake was washed with deionized water until the last washing liquid was neutral. After drying, crushing and sieving through a 100 mesh screen, the acetic ester starch was obtained.
[0052] S2: 500 g of the acetic ester starch and 4.5 L of distilled water were added into a reaction kettle, and gelatinization reaction was carried out at a temperature of 82°C and a rotation speed of 300 r / min for 1 h. Then, the system was cooled to 65°C, and 15 g of ammonium persulfate was added. The initiation was carried out at the temperature and rotation speed for 15 min. Then, a mixed monomer composed of 100 g of acrylic acid (AA) and 66 g of acrylamide (AM) was slowly added dropwise through a constant-pressure dropping funnel within 2 h. After the dropwise addition was completed, the reaction was continuously carried out at 65°C for 3 h. After the reaction was completed, the system was cooled to room temperature to discharge the product. The starch graft polymer solution was obtained.
[0053] S3: 80 g of zeolite powder was added to 800 mL of 10% mass fraction hydrochloric acid solution, and stirred magnetically in a 70°C constant temperature water bath for 2 h. The product was centrifuged, washed with deionized water until the supernatant was neutral, and the washed product was dried at 105°C for 12 h, ground through a 200 mesh sieve, to obtain an acid-treated zeolite powder;
[0054] 60 g of the acid-treated zeolite powder, 6 g of chitosan, and 9 L of 1% mass fraction hydrochloric acid solution were added to a reaction kettle, and continuously reacted at a temperature of 60°C and a rotation speed of 200 r / min for 24 h. The pH value of the system was adjusted to neutral with a 1.25 mol / L sodium hydroxide solution to terminate the reaction. The obtained slurry was subjected to solid-liquid separation, and the solid was vacuum dried, ground, and sieved through a 200 mesh sieve to obtain a chitosan-modified zeolite powder.
[0055] S4: 55 g of the chitosan-modified zeolite powder and 800 mL of deionized water were added to a stirred tank, and sheared at a high speed at a temperature of 50°C and a rotation speed of 800 r / min for 2 h to obtain an inorganic phase suspension. Subsequently, 500 g of a starch graft polymer solution and 55 g of the inorganic phase suspension were added to a reaction kettle, and continuously stirred at a temperature of 60°C and a rotation speed of 600 r / min for 6 h to allow the polymer chains to be fully adsorbed and coated on the surface of the zeolite particles. The above composite slurry was allowed to stand at room temperature for 4 h for curing, and the cured slurry was subjected to suction filtration. The obtained filter cake was washed with deionized water for 3 times, and the washed wet filter cake was dried at a temperature of 60°C. The dried product was ground by a flour mill, and sieved through a 100 mesh sieve to obtain a granular fertilizer special binder.
[0056] Example 4: A preparation method of a granular fertilizer special binder, which is different from example 1 in that the corn starch in step S1 is replaced by an equal amount of cassava starch, and the remaining steps and parameters remain unchanged.
[0057] The substance raw materials used in examples 1-4 of the present application are all commercially available. The corn starch (straight-chain starch content of 25-28%) is purchased from Shanghai Yuanye Biological Co., Ltd.; the cassava starch (purity ≥98%) is purchased from Jiangxi Ruwei Biological Technology Co., Ltd.; the acetic anhydride (analytical pure) is purchased from Tianjin Chemical Reagent Factory No. 1; the ammonium persulfate (reagent grade, 98.5%), acrylic acid (purity >99%), and acrylamide (reagent grade, 99%) are purchased from Shanghai Maikelin Biological Technology Co., Ltd.; the chitosan (degree of deacetylation ≥95%, viscosity 100-200 mPa·s) is purchased from Shanghai Aladdin Biological Co., Ltd.; and the zeolite is purchased from Xiangtan County Tianjie Building Material Processing Factory in Hunan Province, with a particle size of 200 mesh, a total nitrogen content of 0.20 g / kg, a SiO2 content of 70.7%, an Al2O3 content of 19.7%, a pH value of 6.19, and a cation exchange capacity of 128 cmol / g.
[0058] Comparative Example 1: A commercially available clay mineral binder bentonite (sifted through a 100-mesh sieve) was used to replace the granular fertilizer special binder of the present solution, and a binder was obtained.
[0059] Comparative Example 2: On the basis of Example 1, the acetic acid esterification starch paste was gelatinized, and then glutaraldehyde was used as a crosslinking agent to perform a crosslinking reaction. All other steps and parameters remained unchanged, and a binder was obtained.
[0060] Comparative Example 3: On the basis of Example 1, step S3 was omitted, and the starch graft polymer solution obtained in step S2 was directly dried, crushed, and sifted through a 100-mesh sieve in step S4, and a binder was obtained.
[0061] Comparative Example 4: On the basis of Example 1, the chitosan modification operation after acid treatment of the zeolite was omitted, and in step S4, the acid-treated zeolite powder was directly used to configure an inorganic phase suspension with deionized water, and then was compounded with the starch graft polymer solution. All other steps and parameters remained unchanged, and a binder was obtained.
[0062] The binders prepared in Examples 1-4 and Comparative Examples 1-4 were used to prepare granular fertilizer samples, and the preparation steps are as follows:
[0063] One kilogram of commercially available urea-based nitrogen-phosphorus-potassium compound fertilizer (nitrogen-phosphorus-potassium ratio of 28-6-6) sieved through an 80-mesh sieve and 50g of the binder obtained in Examples 1-4 / Comparative Examples 1-4 were first mixed for 15 minutes, and then the uniformly premixed powder was transferred to a table disc granulator. Under slow rotation, a small amount of 150mL deionized water was uniformly sprayed to promote granulation. After uniform granules of 1-4mm were formed, the wet granules were placed in a forced air drying oven at 80°C and dried to constant weight. Finally, the qualified granules of 2-4mm were selected by standard sampling screening, and granular fertilizer samples were obtained.
[0064] The granular fertilizer samples prepared in Examples 1-4 and Comparative Examples 1-4 were tested for performance. The granular compression strength was determined according to the HG / T 2782-2011 standard. Thirty granular fertilizer samples were randomly selected, and the maximum pressure value when each sample was broken was determined using a granular strength tester. The data was recorded and the arithmetic mean value was calculated, which was expressed in Newton (N). The higher the value, the better the mechanical strength of the fertilizer granules prepared from the corresponding binder, and the stronger the anti-crushing and anti-dusting ability during storage, transportation, and application.
[0065] The particle size distribution and the pulverization rate are determined with reference to the GB / T 24891-2010 standard. 100 g of the granular fertilizer sample is placed on the uppermost layer of a set of grading screens with a pore size meeting the standard requirements, and is vibrated and screened on a vibrating screen machine for 5 min. After the screening is completed, the sample mass remaining on each screen surface is weighed, and the percentage of the total mass is calculated to obtain the particle size distribution of the sample. Meanwhile, the mass of the powder collected through the finest layer screen is weighed, and the percentage of the total mass is calculated to obtain the pulverization rate. The lower the particle size distribution and the pulverization rate, the better the granulation performance of the binder, the higher the uniformity of the obtained granules, and the stronger the anti-abrasion and anti-pulverization ability of the granules during storage and transportation, and the more stable the product quality.
[0066] The nutrient slow-release performance is determined with reference to the determination method of the nutrient release rate in the GB / T 23348-2021 standard. 10 g of the granular fertilizer sample is placed in a container with a plug, and is cultured at 25 DEG C in a constant temperature condition. The sample is taken at 1 d, 3 d, 7 d, 14 d and 28 d of the culture, respectively, the cumulative dissolution amount of nitrogen in the culture solution is determined, and the cumulative dissolution rate relative to the total amount of the initial nutrients of the fertilizer is calculated. The lower the dissolution rate in the initial 1-3 d, the slower and more persistent the nutrient release of the fertilizer granules prepared from the binder, the more excellent the nutrient slow-release performance, and the more beneficial to reduce nutrient loss and improve fertilizer utilization.
[0067] The thermal storage stability is simulated by placing each granular fertilizer sample in a constant temperature oven at 54 DEG C for accelerated storage for 14 d. After the storage is completed, the sample is restored to room temperature, and then 30 granules are randomly selected and their compressive strengths are determined one by one according to the standard method in the HG / T 2782-2011 standard. The arithmetic mean value is calculated, and the percentage of the ratio of the compressive strength after the thermal storage to the compressive strength before the thermal storage is the strength retention rate. The higher the strength retention rate, the more stable the chemical structure of the binder in the long-term high-temperature environment, the better the performance, and the more excellent the storage stability of the prepared granular fertilizer.
[0068] All the test results are the average values of three parallel experiments, and the test results are shown in the following table.
[0069] Table Performance test results of each granular fertilizer sample Item group Particle compressive strength (N) Dust rate (%) 7d nitrogen cumulative dissolution rate (%) Strength retention rate after thermal storage (%) Example 1 58.5 2.1 45.2 95.8 Example 2 55.3 2.4 46.8 94.5 Example 3 59.8 1.9 44.5 96.2 Example 4 56.9 2.3 47.1 93.7 Comparative Example 1 28.3 12.5 81.6 85.4 Comparative Example 2 35.2 8.8 78.9 62.3 Comparative Example 3 45.6 4.5 69.5 90.1 Comparative Example 4 52.7 3.0 58.3 92.5
[0070] As shown in Table 1, the granular fertilizer special binders prepared in Examples 1-4 have the organic-inorganic hybrid structure of the flexible bonding network of the starch grafted polymer and the rigid porous framework of the chitosan modified zeolite, and have significant advantages in the particle strength, anti-pulverization, nutrient slow-release and thermal storage stability. The problems of the traditional binders, such as high addition amount, easy pulverization and instability in the high-nitrogen environment, are effectively solved.
[0071] Example 2, by moderately reducing the amount of each reactant and the reaction intensity, its performance is slightly lower but still far superior to the comparative example, to prove the process parameters within a certain range of adjustability; Example 3, by increasing the concentration of the reactants, temperature and time, the optimal comprehensive performance is obtained, especially the particle compressive strength and the heat storage strength retention rate are the highest, which proves that under more sufficient reaction conditions, the three-dimensional hybrid structure formed is more perfect; Example 4 replaces corn starch with cassava starch, its performance is similar to that of Example 1 but slightly fluctuates, indicating that starch raw materials of different sources are applicable in the technical solution, widening the raw material selection range; these examples verify from different angles that the technical solution of the present application has good adjustability and stability.
[0072] Comparative Example 1, due to the use of traditional commercially available bentonite as a binder, its mechanism is relatively single, mainly relying on physical filling and weak electrostatic adsorption, lacking precise chemical bonding and network synergy, resulting in obvious deficiencies in all key performances of the sample, which may be because the traditional clay itself has weak adhesion and poor interface compatibility with the fertilizer particles, unable to build a strong and stable three-dimensional bonding network, its high addition amount not only seriously dilutes the fertilizer nutrients, but also fails to provide effective mechanical support and controlled release barrier, this result proves that relying solely on the physical adhesion function of traditional clay cannot fundamentally solve the core problems of low fertilizer particle strength, easy pulverization and no slow release.
[0073] Comparative Example 2, although it obtains certain bonding strength through chemical crosslinking of glutaraldehyde at the initial stage, but the heat storage strength retention rate decreases sharply, far lower than that of the present application, which may be because in the alkaline ammonia environment of high-nitrogen fertilizer simulation heat storage, the Schiff base side reaction of glutaraldehyde and the hydrolysis of starch molecular chain it triggers, leading to the destruction of the original chemical crosslinking network and the irreversible decline of the bonding performance, this result proves that the chemical crosslinking path using aldehyde crosslinking agent has essential instability in high-nitrogen fertilizer system, unable to meet the stability requirements of long-term storage.
[0074] Comparative Example 3, after completely omitting step S3, the particle compressive strength and slow release performance of its sample are significantly inferior to those of the present application, which may be because of the lack of the three-dimensional rigid skeleton and porous adsorption carrier provided by the acid-activated zeolite, the entire bonding system may be weakened in mechanical support and nutrient release function; for the pure organic starch graft polymer network, it may be more prone to deformation when subjected to external pressure, resulting in relatively insufficient particle strength; at the same time, due to the lack of the adsorption and release effect of the huge specific surface area and pore structure of zeolite on nutrient molecules, the release rate of nutrients is relatively accelerated; this result shows that the introduction of zeolite as an inorganic rigid skeleton is one of the key factors for building the high-performance organic-inorganic hybrid structure described in the present application, thereby achieving excellent mechanical strength and slow release function.
[0075] Comparative Example 4, which omitted the chitosan modification step by directly using acid treatment on the zeolite, had a better comprehensive performance, especially in nutrient release performance, than Comparative Example 3, but was still significantly poorer than all the examples, indicating that simple acid treatment, although it can clean and activate the zeolite surface, lacks the film-forming property, chelation, and more optimized surface chemical properties provided by the chitosan coating, and cannot achieve precise regulation of the nutrient release kinetics. This result demonstrates that the chitosan modification is crucial for fully exerting the dual functions of the zeolite as a controlled-release carrier and a structure enhancer.
[0076] It should be noted that in this document, such terms as "comprise", "comprising", or any other variant thereof, are intended to cover non-exclusive inclusions, so that processes, methods, articles, or devices that include a series of elements not only include those elements, but also include other elements not explicitly listed, or inherent to such processes, methods, articles, or devices.
[0077] Although embodiments of the present application have been shown and described, it is to be understood that various modifications, substitutions, replacements, and variations can be made to these embodiments without departing from the principles and spirit of the present application, which can be understood by those of ordinary skill in the art.
Claims
1. A method for preparing a binder specifically for granular fertilizers, characterized in that, Prepared by the following steps: Step 1: Using corn starch and acetic anhydride as raw materials, an esterification reaction is carried out under the action of an alkaline catalyst to obtain starch acetate. Step 2: Through free radical graft copolymerization, using acrylic acid and acrylamide as comonomers, acrylic acid-acrylamide copolymer side chains are introduced into the acetate starch molecular chain to obtain a starch graft polymer solution. Step 3: Using the principle of electrostatic self-assembly, chitosan is coated onto the surface and pores of acid-activated zeolite to obtain chitosan-modified zeolite. Step 4: By using a composite blending method, an inorganic phase suspension of chitosan-modified zeolite and water is combined with a starch-grafted polymer solution. After maturation, drying, and pulverization, a special binder for granular fertilizer is obtained.
2. The preparation method of a special binder for granular fertilizer according to claim 1, characterized in that, The specific preparation steps of the granular fertilizer binder are as follows: Add the starch-grafted polymer solution and the inorganic phase suspension to a reaction vessel and stir continuously at 50-60℃ and 400-600r / min for 4-6h. Let the resulting composite slurry stand at room temperature for 2-4h to mature. Filter the matured slurry, wash the filter cake, dry it, grind it into fine powder, and pass it through a 100-mesh sieve to obtain a special binder for granular fertilizer. The mass ratio of the starch-grafted polymer solution to the inorganic phase suspension is 80-100:9-11.
3. The method for preparing a special binder for granular fertilizer according to claim 2, characterized in that, The inorganic phase suspension is prepared by mixing chitosan-modified zeolite powder and deionized water in a ratio of 45-55g:500-800mL.
4. The preparation method of a special binder for granular fertilizer according to claim 2, characterized in that, The specific preparation steps of the starch-grafted polymer solution are as follows: Acetate-esterified starch and distilled water were added to a reaction vessel and gelatinized at 78-82℃ and 200-300 r / min for 1 h. The system was then cooled to 60-65℃, ammonium persulfate was added, and the mixture was stirred for 15 min. Acrylic acid and acrylamide were then mixed and added dropwise to the reaction vessel over 1-2 h. After the addition was complete, the reaction was continued for 2-3 h. After the reaction was completed, the mixture was cooled to room temperature and discharged to obtain a starch-grafted polymer solution.
5. The method for preparing a special binder for granular fertilizer according to claim 4, characterized in that, The ratio of acetate-esterified starch, distilled water, ammonium persulfate, acrylic acid, and acrylamide is 400-500g: 3.6-4.5L: 8-15g: 50-100g: 33-66g.
6. The method for preparing a special binder for granular fertilizer according to claim 4, characterized in that, The specific preparation steps of the acetate-esterified starch are as follows: Natural starch and deionized water were added to a reaction vessel and stirred at 200-300 rpm. A 5 wt% sodium carbonate solution was added to adjust the pH of the system to 8-8.
5. Acetic anhydride was slowly added to the vessel over 20-30 minutes at 28-32℃ and 150-250 rpm, while maintaining the pH of the system at 8-8.5 with sodium carbonate solution. After the addition was complete, the reaction was stirred for 1 hour. A 0.5 mol / L dilute hydrochloric acid solution was added to the reaction vessel to adjust the pH to 6.5-7 and terminate the reaction. The mixture was then filtered, and the filter cake was washed with deionized water until the final washing liquid was neutral. The cake was dried, pulverized, and passed through a 100-mesh sieve to obtain acetate starch.
7. The method for preparing a special binder for granular fertilizer according to claim 6, characterized in that, The ratio of corn starch, deionized water, and acetic anhydride is 500-700g: 900-1300mL: 23-32mL; the natural starch is either corn starch or tapioca starch.
8. The method for preparing a special binder for granular fertilizer according to claim 1, characterized in that, The specific preparation steps of the chitosan-modified zeolite are as follows: Acid-treated zeolite powder, chitosan, and a 1% hydrochloric acid solution were added to a reactor and reacted continuously at 60℃ and 100-200 r / min for 24 h. The pH of the system was adjusted to neutral with a 1.25 mol / L sodium hydroxide solution to terminate the reaction. The resulting slurry was subjected to solid-liquid separation. The solid was vacuum dried, ground, and passed through a 200-mesh sieve to obtain chitosan-modified zeolite powder.
9. The method for preparing a special binder for granular fertilizer according to claim 8, characterized in that, The ratio of the acid-treated zeolite powder, chitosan, and hydrochloric acid solution is 50-60g: 5-6g: 7.5-9L; the acid-treated zeolite powder is prepared by mixing zeolite powder and a 10% hydrochloric acid solution at a ratio of 50-80g: 500-800mL.
10. A binder specifically for granular fertilizers, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.
Citation Information
Patent Citations
Adhesive for granular fertilizer and preparation method for adhesive
CN103011959B